REKONSTRUKSI ESTETIKA AKHLAK: Suatu desain pendidikan moral generasi muda kontemporer - Chairan M. Nur (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2016)
Good behavior (akhlÄq) is an action that is acted without any consideration. Good deeds mirror the sincerity of the soul driven from good behaviors. Good behaviorcan not be separated with aesthetics. One action done sincerily yields fineness. Talking in a polite and proper ways evoke lovefrom those who saw it. In reverse, if they speak rudely, people could feel the aura of arrogancy and scary. Those are the strenght of aestahic behaviour that can filter all the deviation of the human being toward misbehavior.